Wireless sensor networks based solution for Harumanis yield monitoring - Harun, A.; Rohani S., Mohamed Farouk; Latifah Munirah, Kamarudin; Ramli, M. F.; Ndzi, D. L.; Ali Yeon, Md Shakaff, Prof. Dr.; Ammar, Zakaria; Mahmad Nor, Jaafar, Prof. Madya Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Man Machine Systems (ICoMMS 2012) organized by School of Mechatronic Engineering, co-organized by The Institute of Engineer, Malaysia (IEM) and Society of Engineering Education Malaysia, 27th - 28th February 2012 at Bayview Beach Resort, Penang, Malaysia.